Mapping religious and civil spaces in traditional and charismatic Christianities in the Philippines - Francisco, Jose Mario C. (2010)
This study of Filipino Christianity focuses on typical constructions of religious space as represented by four constituencies or groups: (a) traditional Catholicism, which defines religious space as enclosed and geographically bound; (b) alternative sects on Mount Banahaw in Southern Luzon, which have moved away from this enclosed space to localize
Christianity; (c) Couples for Christ, a Catholic charismatic group, which extends religious space into the household and the wider world; and (d) El Shaddai, a charismatic group founded by Mike Velarde, which incorporates mass media into its religious space. These constructions of religious space shape each group’s presence and practice in civil space.
Keywords: Sacred spaces; Catholicism; Christianity; Religious communities; Religious facilities; El Shaddai (Prayer movement); Couples for Christ